DETERMINAN FRAUD PADA PENGGUNAAN DANA DESA STUDI KASUS GAMPONG/DESA DI KOTA LANGSA - Kismawadi, Early Ridho (Fakultas Ekonomi dan Bisnis Islam, 2019)
Abstrak This study aims to discuss trends in the use of village funds. Basically, the village government is obliged to prosper the village community with a village fund budget that has been channeled directly by the central government because the village government is directly in contact with rural communities. However, in line with the village budget allocation to the village government more and more fraud has occurred. In the study, measuring the level of fraud on the use of village funds, in this study used two variables, the dependent variable (the tendency of fraud on the use of village funds) and the variable free (the nature of love of money and spiritual intelligence). The results of the regression calculations show that Love of Money (X1) has a partial effect on the Fraud Tendency on the use of village funds. Whereas Spiritual Intelligence (X2) has no partial effect on the Fraud Tendency on the use of village funds.